IgE and T Cell Reactivity to a Comprehensive Panel of Cockroach Allergens in Relation to Disease - Pomés, Anna; Schulten, Véronique; Glesner, Jill; da Silva Antunes, Ricardo; Sutherland, Aaron; Bacharier, Leonard B.; Beigelman, Avraham; Busse, Paula; Frazier, April; Sette, Alessandro (Frontiers in Immunology, 2021)
IgE sensitization to cockroach allergens is associated with development of allergic diseases, such as asthma. To understand the relevance of different cockroach allergens for diagnosis and immunotherapy, a comprehensive analysis of IgE antibody levels and T cell reactivity to an expanded set of cockroach allergens and their relationship to disease was performed in a cohort of USA cockroach sensitized patients. IgE antibody levels to recombinant chitinase and hemocyanin were measured for 23 subjects by custom-made ImmunoCAPs and compared with IgE levels to 8 cockroach allergens we previously reported for the same cohort. Ex vivo T cell activation (Ox40/PDL-1 expression) of PBMCs stimulated with peptide pools derived from 11 German cockroach proteins, including 9 official cockroach allergens, plus chitinase and vitellogenin, was determined by flow cytometry. IgE prevalences to chitinase (17%) and hemocyanin (44%) were comparable to values for the other 8 allergens that we previously reported (21-57%). Hemocyanin (Bla g 3), was a major allergen (one to which more than 50% of patients with an allergy to its source react) for a sub-group of 15 highly cockroach-sensitized subjects (IgE > 3.5kUA/L: 53%). Chitinase was officially named as new allergen Bla g 12. Cockroach-specific IgE levels in plasma showed excellent correlation with the sum of 10 allergen-specific IgE (r=0.94, p < 0.001). T cell reactivity to 11 proteins was highly variable among subjects, the highest being for vitellogenin, followed by Bla g 3. The main finding was that cockroach allergen-specific IgE and T cell reactivity patterns were unique per subject, and lacked immunodominant allergens and correlation with clinical phenotype/disease severity in the studied cohort. Knowing the subject-specific B/T cell reactivity profiles to a comprehensive panel of cockroach allergens will contribute to diagnosis of cockroach allergy and will be important for planning and assessing allergen immunotherapy outcomes, according to the allergen content in therapeutic cockroach extracts.